Stated choice methods : analysis and applications - Louviere, Jordan J. (Cambridge University Press, 2000)
This graduate and practitioner guide to analysing consumer choice behaviour concentrates on stated preference (SP) methods. The authors show how these methods can be implemented, from experimental design to econometric modelling, and also combined with revealed preference (RP) data. The book also presents an update of econometric approaches to choice modelling.